CONCEPTUAL BASES FOR STRATEGIC COOPERATION BETWEEN LAW ENFORCEMENT AGENCIES IN THE CONTEXT OF THE MODERNISATION OF PUBLIC ADMINISTRATION IN UKRAINE - Honiukova, Liliia; Kozhyna, Alla (Public Management and Policy, 2026)
This article provides a comprehensive theoretical justification of the conceptual foundations of strategic cooperation between law enforcement agencies as a key element in the modernization of the public administration system in Ukraine. It is demonstrated that the contemporary paradigm of statehood development, in the context of martial law and the intensification of European integration processes, requires a systematic transition to a service-oriented model of operation for law enforcement institutions, where the protection of the rights, freedoms and interests of individuals and citizens is an absolute priority. Particular attention is paid to the introduction of innovative tools for strategic management and forecasting in the activities of law enforcement agencies. The feasibility of applying the Forsythe methodology for designing scenarios of crime-prone situations and developing a long-term vision for the future of the law enforcement system is substantiated. The concept of ‘managerial resonance’ is explored as a necessary condition for synchronizing the efforts of administratively independent law enforcement agencies to overcome ‘departmental fragmentation’ and achieve a common strategic goal. The paper makes a case for the need to institutionalize cooperation through the establishment of a National Coordinator for Law and Order. Its functional parameters are defined: from the creation of a unified information and communication space and real-time data exchange to the coordination of agencies’ communication strategies to ensure a unified state narrative. Aspects of legal convergence with European Union standards and the implementation of the EU acquis into domestic practice have been analyzed. The key principles of strategic cooperation have been identified and detailed: systematicity, dialogue, openness and innovation. A model of digital interaction between actors based on analytically driven law enforcement activities is proposed. The proposed conceptual approach will enable the formation of a highly mobile and resilient mechanism for ensuring law and order, adapted to the complex challenges of wartime and post-war periods.